1997
DOI: 10.1007/s004240050306
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the L-type calcium channel by the five muscarinic receptors (m1-m5) expressed in NIH 3T3 cells

Abstract: Modulation of L-type calcium channels by the five cloned muscarinic receptors was studied by expression of the receptors in NIH 3T3 cells. Application of acetylcholine (ACh) to cells transfected with m1-m5 resulted in a reduction in the L-type calcium current amplitude. Elevations in intracellular cAMP concentrations induced by 8-bromo-cAMP or forskolin resulted in no discernible change in the L-type calcium current. In addition, treatment with Rp-adenosine 3',5'-cyclic monophosphothioate triethylamine (Rp-cAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
1
22
2
Order By: Relevance
“…In this respect, our present results have provided the intriguing possibility that a muscarinic receptor pharmacologically indistinguishable from the M5 receptor upregulates L-type Ca 2+ channel activities via activation of a specific PKC pathway and may contribute to enhancing the gastric motility (see below). Recently, modulation of Ltype Ca 2+ channels by muscarnic receptors was investigated by recombinantly expressing five subtypes of muscarinic receptors (m1 -m5) into an established fibroblast cell line, NIH 3T3 cells (28). Somewhat unexpectedly, stimulation of PI turnover-linked receptors, i.e., m1, m3 and m5 receptors by ACh all resulted in inhibition of Ca 2+ currents via activation of PKC, thus seemingly contradicting the results of the present study.…”
Section: +contrasting
confidence: 96%
“…In this respect, our present results have provided the intriguing possibility that a muscarinic receptor pharmacologically indistinguishable from the M5 receptor upregulates L-type Ca 2+ channel activities via activation of a specific PKC pathway and may contribute to enhancing the gastric motility (see below). Recently, modulation of Ltype Ca 2+ channels by muscarnic receptors was investigated by recombinantly expressing five subtypes of muscarinic receptors (m1 -m5) into an established fibroblast cell line, NIH 3T3 cells (28). Somewhat unexpectedly, stimulation of PI turnover-linked receptors, i.e., m1, m3 and m5 receptors by ACh all resulted in inhibition of Ca 2+ currents via activation of PKC, thus seemingly contradicting the results of the present study.…”
Section: +contrasting
confidence: 96%
“…L-type channels appear to be a consistent target for the inhibitory action of protein kinase C activators in several Ž cell types Haymes et al, 1992;Bouron et al, 1995; . Pemberton and Jones, 1997;Zhang et al, 1997 . Consistent with the results described in this study, we have previously reported that PMA inhibits high K q -evoked Ž catecholamine release from bovine chromaffin cells 23-. Ž .…”
supporting
confidence: 81%
“…Ž 1993 or inhibition Rane et al, 1989;Chik et al, 1996; . Pemberton and Jones, 1997;Redman et al, 1997 of depolarization-evoked Ca 2q currents, depending on the cell type. In chromaffin cells, protein kinase C activation Ž either has no effect Burgoyne and Norman, 1984;Morita .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies support a role for PKC in the enhancement (Swartz, 1993;Yang and Tsien, 1993;Kamatchi et al, 2003) or inhibition (Pemberton and Jones, 1997;Rane and Dunlap, 1986) of depolarization-evoked Ca v currents by DAG, PMA or MCh. Although the auxiliary β subunit is required for this action (Stea et al, 1995;Kamatchi et al, 2003) most evidence suggests that PKC targets the α 1 subunit.…”
Section: Discussionmentioning
confidence: 94%